2021
DOI: 10.3390/ani11082170
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Zinc Oxide Nanoparticles on the Embryo of Javanese Medaka (Oryzias javanicus Bleeker, 1854): A Comparative Study

Abstract: (1) Background: Zinc oxide nanoparticles (ZnO NPs) are widely applied in various human products. However, they can be extremely toxic for aquatic organisms, particularly fish. This research was conducted to determine the LC50 of ZnO NPs on the embryos of Javanese medaka (Oryzias javanicus) in ultra-pure, deionized, and dechlorinated tap water; (2) Methods: The experiments were conducted in a completely randomized design (CRD) with three replicates for six treatments for acute (0.100, 0.250, 0.500, 1.00, 5.00, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…The TEM image of ZnO-NPs used in the present study was shown in Figure S1 . A previous study also reported the TEM image and X-ray diffraction (XRD) results of ZnO-NPs [ 33 ]. The concentrations of Zn released from ZnO-NPs in a Luria–Bertani broth (LB) medium during the 8 h E. coli exposure period were determined at 0, 4, 6, and 8 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The TEM image of ZnO-NPs used in the present study was shown in Figure S1 . A previous study also reported the TEM image and X-ray diffraction (XRD) results of ZnO-NPs [ 33 ]. The concentrations of Zn released from ZnO-NPs in a Luria–Bertani broth (LB) medium during the 8 h E. coli exposure period were determined at 0, 4, 6, and 8 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were induced to five distinct exposure levels of ZnO NPs (10, 25, 50, 100, and 150 µg/L). In our earlier work, the characterization of ZnO NPs for size in powder form using an X-ray diffraction spectrometer (XRD), shape or morphology using transmission electron microscopy (TEM), and size distribution and surface charge using dynamic light scattering (DLS) was already reported (Amin et al, 2021).…”
Section: Zinc Oxide Nps Stock Preparation and Characterizationmentioning
confidence: 99%
“…Organic-based NPs, for example, dendrimers, micelles, liposomes, and polymer NPs, constitute a separate category. Additionally, compositebased NPs are another type that can be categorized based on their structural constituents (Amin et al, 2021). The hazards and advantages of these new materials have been extensively debated.…”
Section: Introductionmentioning
confidence: 99%
“…After multiple bending and periodic turbulence impact, the nanoparticles in the filters easily fell off from the matrix and then breathed into the human body through the respiratory tract. These nanoparticles aggregating in human tissues lead to local inflammation in human tissue cells through ion precipitation, oxidative stress, and other reactions, thereby affecting the normal gene expression and physiological metabolism of cells causing serious disease manifestations. , It has been found that the morphology, particle size, contact time, and concentration of nanoparticles have potential toxicity to biological cells . Therefore, the reduction of nanoscaled agents on filters is essential to seek a high-efficient antibacterial agent with a size greater than the pore of the filter.…”
Section: Introductionmentioning
confidence: 99%